Bancada teste para ensaio de lubricidade: desenvolvimento do sistema para medição de torque e validação dos resultados - Gualberto, Victor Soares (2022)
During the operation of all mechanical equipment, there are always parts in contact, more or less intensively, where there is a need for lubrication to reduce the wear caused by contact. Concurrent with this need for lubrication, there is an incessant search for renewable fuels and lubricants that are not harmful to the environment and, at the same time, meet the market's lubrication needs. Whenever there is the development of these new compounds, it is necessary to carry out tests, among them, the tribological test, whose purpose is to evaluate the fluid lubricity and measure the wear of the parts that are in contact, and the pressure drop tests. Therefore, there is also a need to use a mechanical system capable of allowing these analyzes to be carried out together with the variation of test parameters. In this work, experiments were carried out on a tribological workbech configured as Timken® whose objective is to evaluate the lubricity of the lubricant or fuel in question. This bench analyzes the lubricity using a 2 N.m rotary torque transducer connected to two shafts at both ends. For the collection of torque data, an Arduino® Uno was used. In addition, tribological tests were also carried out on a Discovery HR-3 rheometer, standardized, configured with the Four Ball arrangement in order to compare the performance of the new tribological workbench with a standardized machine. Two types of oils were used: mineral oil SAE 20W50, used for lubricating single-cylinder four-stroke motorcycle engines, and synthetic oil SAE 5W40, whose application is recommended for lubricating high-performance four-stroke motorcycle engines. It was verified that the mineral oil, for the test carried out, in the machine developed, presented the lowest torque values, 0.14 Nm, and the synthetic oil presented a torque value of 0. 24 Nm, due to its thick protective layer between the surfaces in contact, mainly due to its higher viscosity compared to synthetic oil. In addition, samples lubricated with mineral oil also showed lower wear values compared to synthetic oil, being 203.64 µm for samples lubricated with mineral oil and 238 µm for samples lubricated with synthetic oil. As for the tests carried out in the rheometer configured with the Four Ball, the mineral oil samples showed torque and wear in the value of 17549.4 µN.m and 209.89 µm, respectively, against 17579.8 µN.m and 224.45 µm, respectively, of synthetic oil. Furthermore, the new workbench presented the mineral oil as the oil, according to the test conditions and according to the purpose of the study, with better lubricity performance, due to its physicochemical properties, as well as the standardized machine with the Four Ball configuration.